Evaluation of a new concept of immune-enhancing diet in a model of head-injured rat with infectious complications: A proof of concept study. Issue 6 (December 2016) - Charrueau, Christine; Moinard, Christophe; Brinkmann, Saskia; Choisy, Caroline; Butel, Marie-José; Bureau, Michel-Francis; Le Plénier, Servane; Brignole-Baudouin, Françoise; Neveux, Nathalie; Cynober, Luc; De Bandt, Jean-Pascal
Summary: Immune-enhancing diet (IED) utilization in critically ill septic patients is still debated. A new concept of IED has been proposed combining extra glutamine sequentially with either antioxidants or other amino acids, in order to match patient requirements according to their response to injury. We evaluated whether this new IED elicits a more favorable response to stress when compared with two existing IEDs both enriched in arginine but with different levels of anti-oxidants, in a validated rat model combining head injury (HI) and infectious complications. Forty-eight HI rats were randomized into four groups ( n  = 11–13 per group) to receive, for 4 days, standard enteral nutrition (S), one of the two existing IEDs (IED1, IED2), or the new IED (IED3; providing glutamine and antioxidants for two days and glutamine and specific amino acids for two days). Two days after HI, the rats received an enteral bolus of luminescent Escherichia coli Xen14 to induce infection, and bacterial dissemination was evaluated. Body weight (BW) was recorded daily. Four days after HI, animals were euthanized; blood was sampled; organs were weighed; cumulated nitrogen balance (CNB) and nitrogen efficiency were determined. IED3 was more efficient than IED1 and IED2 in improving BW recovery from D3 (D3 vs . D1, p  < 0.05) after HI. It significantly improved CNB and net protein utilization (IED3 vs. S, IED1, IED2, p  < 0.05). An IED with sequential administration of anti-oxidants and glutamine may be better suited to meeting nutritional requirements in severe catabolic states.